Comment on ‘The spectral decomposition of the helium atom two-electron configuration in terms of hydrogenic orbitals’ - Di Rocco, Hector Omar (2013)
A brief remark is made about Hutchinson´s paper et al (2012 E.J.P) about the ground configuration of the Helium atom and the importance of continuum states. The purpose of our comment is twofold: first, to indicate that even using good basis set, obtained by the Self-Consistent Hartree-Fock method, the contribution of other bound states and continuum ones is of some importance to calculate energy levels; on the other hand, to emphasize that continuum states can be of great importance to satisfy several rigurous sum rules.